Acrylic copolymer as well as composition and application thereof
By combining acrylic copolymers with bisaziridine compounds, the problem of poor dispersion of single-wall carbon nanotubes in water is solved, and uniform dispersion and stable existence are achieved in the negative electrode of lithium battery, thereby improving the performance of the negative electrode sheet.
Patent Information
- Application Number
- CN202411899660.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-23
Smart Images

Figure BDA0005202810400000051 
Figure BDA0005202810400000091 
Figure BDA0005202810400000101
Abstract
Description
Technical Field
[0001] The invention relates to an acrylic copolymer, in particular to an acrylic copolymer capable of improving the dispersibility of single-walled carbon nanotubes. Background Art
[0002] Lithium-ion batteries are widely used in various fields such as smart phones, tablets, and automobiles. Lithium-ion batteries are composed of positive electrode sheets, negative electrode sheets, diaphragms, electrolytes, and shells. Among them, negative electrode materials are developing towards high energy density, upgrading from graphite negative electrodes to silicon-based negative electrodes. The theoretical capacity of silicon-based negative electrodes is about 3758mAh / g, which is 10 times that of commercial graphite. Since the lithium storage mechanism of single silicon is a typical alloying / de-alloying mechanism in lithium-ion batteries, the huge lithium insertion capacity and the complex phase transition of LixSi will cause the silicon negative electrode material to experience severe volume expansion (nearly 300%) and structural changes during the lithium insertion and de-insertion process. Volume expansion will cause cracks in silicon-based negative electrode materials until they are pulverized, destroying the electrical contact between active substances, electrode materials, and current collectors, increasing internal resistance, and rapidly decaying battery capacity.
[0003] As a new type of nanomaterial, single-walled carbon tubes have excellent electrical conductivity and mechanical properties. Structurally, the high aspect ratio leads to a good three-dimensional conductive network under the condition of very small addition amount, and can also inhibit the expansion of silicon negative electrode. As a high-kinetic conductive additive, single-walled carbon tubes face two major problems when applied to silicon negative electrodes: on the one hand, their strong hydrophobicity makes it difficult to disperse in water; on the other hand, due to poor compatibility with adhesives, they also face the risk of precipitation in the slurry. At present, most studies have achieved the dispersion of single-walled carbon nanotubes in water by grafting modified hydrophilic functional groups, but the surface grafting functional groups can easily destroy the conductive network of single-walled carbon nanotubes. The dispersant prepared by physical interaction is very easy to exist in the water phase when it is highly hydrophilic, and the strong van der Waals force between carbon nanotubes causes them to re-aggregate; when the dispersant is highly hydrophobic, it exists in the carbon nanotube aggregates and cannot be stably present. Therefore, balancing the hydrophilicity and hydrophobicity of the dispersant and developing single-walled carbon nanotube dispersants are the key to the large-scale application of single-walled carbon nanotubes in negative electrodes. Summary of the invention
[0004] In order to overcome at least one defect of the above-mentioned prior art, in the first aspect, an embodiment of the present invention provides an acrylic copolymer, which is prepared by polymerizing monomers; the polymerized monomers include carboxylic acids containing carbon-carbon double bonds, acrylonitrile, styrene, acrylamide, acrylic esters, itaconic acid diesters and amphiphilic monomers containing carbon-carbon double bonds;
[0005] The amphiphilic monomer containing carbon-carbon double bonds includes one or more of acrylic acid polyether phosphate, diisooctyl maleate, allyloxy nonylphenol polyoxyethylene ether, and 2-acrylamide-2-methylpropane sulfonic acid.
[0006] In a second aspect, an embodiment of the present invention provides an acrylic copolymer composition, comprising the acrylic copolymer described above and a cross-linking agent, wherein the cross-linking agent comprises a difunctional diaziridine compound.
[0007] In a third aspect, an embodiment of the present invention provides the use of the above-mentioned acrylic copolymer or the above-mentioned acrylic copolymer composition as a dispersant for single-walled carbon nanotubes or for preparing a negative electrode for a lithium battery.
[0008] In a fourth aspect, an embodiment of the present invention provides a single-walled carbon nanotube dispersion, comprising the above-mentioned acrylic copolymer or a combination of the above-mentioned acrylic copolymers and single-walled carbon nanotubes.
[0009] In a fifth aspect, an embodiment of the present invention provides a negative electrode slurry, comprising the above-mentioned acrylic copolymer composition or the above-mentioned single-walled carbon nanotube dispersion.
[0010] In a sixth aspect, an embodiment of the present invention provides a negative electrode plate, the raw materials for preparing the negative electrode plate include the negative electrode slurry mentioned above.
[0011] In a seventh aspect, an embodiment of the present invention provides a lithium battery, comprising the above-mentioned negative electrode plate.
[0012] The acrylic copolymer according to one embodiment of the present invention can be used as a dispersant for single-walled carbon nanotubes, and can make the single-walled carbon nanotubes have a good dispersion state in water. DETAILED DESCRIPTION
[0013] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions therein are essentially used as illustrations rather than to limit the present invention.
[0014] An embodiment of the present invention provides an acrylic copolymer, which is prepared by polymerizing monomers; wherein the polymerized monomers include carboxylic acids containing carbon-carbon double bonds, acrylonitrile, styrene, acrylamide, acrylate, itaconate diester, and amphiphilic monomers containing carbon-carbon double bonds;
[0015] The amphiphilic monomer containing a carbon-carbon double bond includes one or more of acrylic acid polyether phosphate, diisooctyl maleate, allyloxy nonylphenol polyoxyethylene ether, and 2-acrylamide-2-methylpropane sulfonic acid.
[0016] In one embodiment, based on the total mass of the polymerized monomers, the mass content of the carboxylic acid containing carbon-carbon double bonds is 30-40%, for example 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%.
[0017] In one embodiment, based on the total mass of the polymerized monomers, the mass content of acrylonitrile is 20-35%, for example 21%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 34%.
[0018] In one embodiment, based on the total mass of the polymerized monomers, the mass content of styrene is 5-10%, for example, 6%, 7%, 8%, or 9%.
[0019] In one embodiment, based on the total mass of the polymerized monomers, the mass content of acrylamide is 8-12%, for example, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%.
[0020] In one embodiment, based on the total mass of the polymerized monomers, the mass content of the acrylate is 15-20%, for example, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%.
[0021] In one embodiment, based on the total mass of the polymerized monomers, the mass content of itaconate diester is 4-8%, for example, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%.
[0022] In one embodiment, based on the total mass of the polymerized monomers, the mass content of the amphiphilic monomer containing carbon-carbon double bonds is 2-6%, for example, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%.
[0023] In one embodiment, the amphiphilic monomer containing a carbon-carbon double bond can be one or more of acrylic acid polyether phosphate, diisooctyl maleate, allyloxy nonylphenol polyoxyethylene ether, and 2-acrylamido-2-methylpropane sulfonic acid. Further, the weight average molecular weight of acrylic acid polyether phosphate can be 200 to 3000, such as 300, 500, 600, 800, 1000, 1500, 2000, 2500; the weight average molecular weight of allyloxy nonylphenol polyoxyethylene ether can be 200 to 3000, such as 300, 500, 600, 800, 1000, 1500, 2000, 2500.
[0024] In one embodiment, the carboxylic acid containing a carbon-carbon double bond contains 3 to 6 carbon atoms (eg, 4 carbon atoms, 5 carbon atoms). Further, the carboxylic acid containing a carbon-carbon double bond contains one carbon-carbon double bond and one or two carboxyl groups.
[0025] In one embodiment, the carboxylic acid containing a carbon-carbon double bond includes one or more of acrylic acid, methacrylic acid, itaconic acid, crotonic acid, fumaric acid, and maleic acid.
[0026] In one embodiment, the acrylate includes one or more of ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, and isooctyl methacrylate.
[0027] In one embodiment, the itaconate diester may be dibutyl itaconate.
[0028] One embodiment of the present invention provides an acrylic copolymer composition, comprising the acrylic copolymer and a cross-linking agent, wherein the cross-linking agent comprises a difunctional diaziridine compound.
[0029] In one embodiment, based on the total mass of the polymerized monomers of the acrylic copolymer, the mass content of the crosslinking agent in the composition is 0.2-0.5%, for example, 0.3% or 0.4%.
[0030] In one embodiment, the difunctional bis-aziridine compound contains two nitrogen heterocyclic structures and at least two trifluoromethyl groups. For example, the difunctional bis-aziridine compound can be 3,3'-((perfluoropropane-2,2-diyl)bis(4,1-phenylene)-3H-diazetidine) as shown in Formula 1 and / or bis(2-((4-(3-(trifluoromethyl)-3H-diazetidine-3-yl)benzyl)oxy)ethyl)amine as shown in Formula 2:
[0031]
[0032] In one embodiment, the acrylic copolymer composition includes an acrylic copolymer, a crosslinking agent, and water, that is, the acrylic copolymer composition is a solution or dispersion containing the acrylic copolymer and the crosslinking agent.
[0033] In one embodiment, the acrylic copolymer composition is an aqueous solution or aqueous dispersion comprising an acrylic copolymer and a crosslinking agent, and its non-volatile matter content or solute content can be 2 to 6 wt%, such as 3 wt%, 4 wt%, 5 wt%; and the pH value can be 7 to 9, such as 8.
[0034] One embodiment of the present invention provides a single-walled carbon nanotube dispersion, comprising the above-mentioned acrylic copolymer and single-walled carbon nanotubes.
[0035] In one embodiment, the single-walled carbon nanotube dispersion includes the above-mentioned acrylic copolymer composition and single-walled carbon nanotubes.
[0036] In one embodiment, the single-walled carbon nanotube dispersion can be used to prepare negative electrode sheets for lithium batteries.
[0037] In one embodiment, in the single-walled carbon nanotube dispersion, the mass content of the single-walled carbon nanotubes may be 0.2-0.4%, such as 0.3%; the mass content of the acrylic copolymer may be 0.4-0.8%, such as 0.5%, 0.6%, 0.7%.
[0038] One embodiment of the present invention provides the use of the acrylic copolymer or a composition thereof as a dispersant for single-walled carbon nanotubes or for preparing negative electrode slurry for lithium batteries.
[0039] In an acrylic copolymer of one embodiment, the carboxylic acid structure containing a carbon-carbon double bond can provide a strong hydrophilic effect, the acrylate structure and the single-walled carbon nanotube can form a strong adsorption effect, and the amphiphilic structure containing a carbon-carbon double bond can play a thickening role to improve the stability of the dispersion; at the same time, in the preparation process of the acrylic copolymer, the amphiphilic monomer containing a carbon-carbon double bond also plays an emulsifying role in the initial stage of the preparation reaction. Among them, the carboxylic acid structure containing a carbon-carbon double bond is a structure formed after the carboxylic acid containing a carbon-carbon double bond is polymerized, the acrylate structure is a structure formed after the acrylate is polymerized, and the amphiphilic structure containing a carbon-carbon double bond is a structure formed after the amphiphilic monomer containing a carbon-carbon double bond is polymerized.
[0040] One embodiment of the present invention provides a method for preparing the acrylic copolymer, comprising: mixing a pre-emulsion with an initiator to carry out a polymerization reaction; wherein the pre-emulsion includes a polymerization monomer.
[0041] One embodiment of the present invention provides a method for preparing the above-mentioned acrylic copolymer composition, comprising: mixing a pre-emulsion with an initiator to carry out a polymerization reaction; wherein the pre-emulsion includes a polymerization monomer and a difunctional diaziridine compound as a crosslinking agent.
[0042] In one embodiment, the difunctional diaziridine compound as a crosslinking agent will not participate in the polymerization reaction of the polymerizable monomers. It is added to the pre-emulsion for the convenience of subsequent use. The crosslinking agent can also be added after the polymerization reaction is completed.
[0043] In one embodiment, the method for preparing the acrylic copolymer comprises the following steps:
[0044] S1: mixing the polymerization monomer and water (e.g., deionized water) to prepare a pre-emulsion;
[0045] S2: dissolving the initiator in water (e.g., deionized water) to prepare an initiator solution;
[0046] S3: adding part of the pre-emulsion and part of the initiator solution into a reactor to perform bottom polymerization;
[0047] S4: dropping the remaining pre-emulsion and the remaining initiator solution into the reactor to carry out dropwise polymerization;
[0048] S5: keeping the solution obtained in step S4 warm to eliminate residual monomers;
[0049] S6: adding alkaline solution to the system of step S5 for neutralization to obtain a dispersant acrylic copolymer composition.
[0050] In one embodiment, the reaction temperature of step S3 can be 80-90°C, for example, 82°C, 84°C, 85°C, 86°C, 88°C; the reaction time can be 15-30 min, for example, 18 min, 20 min, 22 min, 25 min.
[0051] In one embodiment, the reaction temperature of step S4 can be 82-88°C, for example, 82°C, 84°C, 85°C, 86°C; the reaction time can be 150-240min, for example, 160min, 170min, 180min, 190min, 200min, 220min.
[0052] In one embodiment, the initiator is selected from one or more of potassium persulfate, sodium persulfate, and ammonium persulfate.
[0053] In one embodiment, the mass content of the initiator is 0.2-0.5% based on the total mass of the polymerized monomers.
[0054] In one embodiment, the method for preparing the acrylic copolymer comprises the following steps:
[0055] S1: adding the amphiphilic monomer containing carbon-carbon double bonds and deionized water into a pre-emulsification kettle and fully dissolving them uniformly, adding other polymerizable monomers under stirring, and stirring for 10 to 30 minutes to obtain a pre-emulsion;
[0056] S2: dissolving the initiator in water to prepare an initiator solution; wherein the mass ratio of the initiator to water is 1:10-20, and 30-40% is taken as the bottom initiator;
[0057] S3: adding 2-6% of the pre-emulsion prepared in step S1 into a reaction kettle, heating it to 80-90° C., and simultaneously quickly adding the bottom initiator, and keeping the temperature for 15-30 minutes to perform bottom polymerization;
[0058] S4: controlling the reaction temperature of the reactor to 82-88° C., dropping the remaining initiator and pre-emulsion into the reactor for dropwise polymerization, and the dropping time is 150-240 min;
[0059] S5: After the dropwise addition is completed, the system in the reactor is kept warm for 1 to 2 hours, filtered and washed 2 to 3 times, and the filtered solid is retained in the reactor;
[0060] S6: adding deionized water and lithium hydroxide monohydrate to the system in the reaction kettle for neutralization, adjusting the non-volatile matter content to 2-6 wt % and the pH to 7-9.
[0061] One embodiment of the present invention provides a negative electrode slurry, including the acrylic copolymer or a composition thereof or the single-walled carbon nanotube dispersion.
[0062] In one embodiment, the negative electrode slurry includes a negative electrode active material, a conductive agent and a binder, the negative electrode active material includes silicon carbide and graphite, and the conductive agent includes a single-walled carbon tube dispersion.
[0063] In one embodiment, the binder may be a linear polyacrylic acid negative electrode binder, and the conductive agent may be a single-walled carbon tube dispersion or a mixture of a single-walled carbon tube dispersion and conductive carbon black.
[0064] An embodiment of the present invention provides a negative electrode plate, the raw materials for preparing the negative electrode plate include the negative electrode slurry mentioned above.
[0065] In one embodiment, the negative electrode slurry is coated on the current collector and dried to obtain the negative electrode sheet. Furthermore, the dried negative electrode sheet can be energized for activation. Under the action of energization, the crosslinking agent is inserted into the adjacent CH structures in the acrylic copolymer to cause molecular crosslinking, and carbene free radicals are generated to initiate curing and form bonds with the current collector, thereby increasing the interaction between the negative electrode current collector (such as copper foil) and the negative electrode active material.
[0066] In one embodiment, the current collector may be one of a copper foil or a carbon-coated copper foil.
[0067] An embodiment of the present invention provides a lithium battery, comprising the above-mentioned negative electrode plate.
[0068] An acrylic copolymer or a composition thereof according to an embodiment of the present invention can be used as a dispersant for single-walled carbon nanotubes, and can make the single-walled carbon nanotubes have a good dispersion state (e.g., uniform dispersion) in water. Among them, the carbon chain structure of the itaconate diester structure in the acrylic copolymer has a strong interaction with the single-walled carbon nanotubes, and the carbon chain will enter the single-walled carbon nanotube clusters, weakening the van der Waals interaction between the carbon nanotubes under the action of the hydrophilic group. Therefore, the itaconate diester structure can make up for the shortcomings of insufficient adhesion between other structures of the acrylic copolymer and the single-walled carbon nanotubes, and achieve strong adhesion with the single-walled carbon nanotubes, so that the single-walled carbon nanotubes can be uniformly dispersed in the aqueous phase and have good stability.
[0069] Existing dispersants used in electrode slurries are mostly small molecule dispersants, which are easily oxidized and reduced in lithium batteries, resulting in electrical performance degradation. The acrylic copolymer dispersant of one embodiment of the present invention has a strong hydrophilic and single-walled carbon nanotube-philic structure, which can make the single-walled carbon nanotubes have a good dispersion state in water, thereby improving the performance of the prepared negative electrode sheet.
[0070] An acrylic copolymer composition according to an embodiment of the present invention, wherein the acrylic copolymer has good water solubility; the difunctional diaziridine compound generates carbene free radicals under electrical excitation, which can not only interact by inserting into adjacent CH structures to form a strong cohesive effect, but also form a bond with the current collector of the electrode to form a good bond. Therefore, the single-walled carbon tube dispersion containing the composition has a good dispersion effect, and after the electrode pole piece is prepared using the dispersion, the bonding ability between the electrode slurry solidified layer and the current collector can be significantly improved by electrical activation.
[0071] The negative electrode slurry according to one embodiment of the present invention can improve the performance of the prepared negative electrode and the comprehensive performance of the lithium battery by using the single-walled carbon nanotube dispersion.
[0072] The acrylic copolymer of one embodiment of the present invention is applied to the preparation of lithium battery silicon-based negative electrode sheets to make the single-walled carbon tubes disperse evenly, so that the negative electrode sheets have a better state and can also make the negative electrode sheets have a stronger peeling force.
[0073] The preparation and application of the acrylic copolymer composition according to one embodiment of the present invention are further described below in conjunction with examples. The raw materials and test methods involved in each example and comparative example are as follows.
[0074] raw material
[0075]
[0076]
[0077] Test Method
[0078] 1. Non-volatile content test of single-walled carbon nanotube dispersion
[0079] Aluminum foil is made into a weighing dish with a diameter of 5 cm and a height of about 3 cm. It is kept constant in an oven and cooled to room temperature in a desiccator. Its mass is weighed and recorded as m0, accurate to 0.1 mg. With the same accuracy, (2±0.05) g of the sample to be tested is weighed into the weighing dish and recorded as m1 (the sample mass is generally (1±0.05) g). The sample is evenly dispersed on the bottom of the weighing dish. Then, the weighing dish containing the sample is placed in a blast oven preheated to 150°C. After the temperature is restored, the timing is started and the drying is performed for 40 minutes. Take out the sample, put it in a desiccator and cool it to room temperature, and its mass is weighed and recorded as m2.
[0080] Wherein, the non-volatile content X of the upper liquid or lower liquid of the dispersion is:
[0081] X=(m2-m0) / m1×100%.
[0082] X is the mass fraction of non-volatile matter in the sample (%);
[0083] m0 is the mass of the weighing dish, in g;
[0084] m1 is the weight of the sample, in g;
[0085] m2 is the mass of the sample and weighing dish after heating, in g.
[0086] 2. Test of 180° peeling force of negative electrode sheet
[0087] The negative electrode sheet obtained after coating and drying was cut into 1.5 cm × 20 cm strips and rolled with a roller at 1 × 10 5 N / m load roller press twice, use double-sided tape to stick the electrode to a 2mm thick steel plate, stick one side of the coating after the slurry is cured to the steel plate, and use a tensile testing machine to test the coating at a speed of 50mm / min to peel it off in the 180° direction to obtain the peeling force before electrical activation;
[0088] After the negative electrode sheet obtained after coating and drying was activated by a 2V voltage for 2 minutes, the peeling force was tested using the above method to obtain the peeling force after electrical activation.
[0089] Example
[0090] Preparation of acrylic copolymer composition (dispersant)
[0091] S1: At room temperature and pressure, add Ag amphiphilic monomer containing carbon-carbon double bonds and 150g deionized water into a pre-emulsification kettle, mix and dissolve them thoroughly, add Bg acrylate, Cg dibutyl itaconate, Dg acrylamide, Eg acrylonitrile, Fg styrene, Gg carboxylic acid containing carbon-carbon double bonds, and Hg cross-linking agent in sequence under stirring, and stir at 350rpm for 15min to obtain a pre-emulsion.
[0092] S2: Take 1g potassium persulfate and dissolve it in 19g deionized water. After stirring and dissolving, take 8g as the bottom initiator for bottom polymerization and take 12g as the dropwise polymerization.
[0093] S3: At normal temperature and pressure, add 40g of deionized water to the reactor, raise the temperature to 85°C, add 5% of the total mass of the pre-emulsion prepared in step S1 to the reactor, and quickly add 8g of the initiator solution reserved in step S2, and keep the reactor warm for 20min.
[0094] S4: Control the reaction temperature to 85° C., and simultaneously drop the remaining pre-emulsion and the reserved dropwise initiator in step S2 into the reactor, with a total dropwise addition time of 180 min.
[0095] S5: After the dropwise addition is completed, the reactor is kept at 85°C for 1 hour, filtered and washed 2 to 3 times, and the filtered solid is retained in the reactor.
[0096] S6: When the temperature of the reaction kettle system drops to 75° C., lithium hydroxide monohydrate solution is added dropwise thereto to adjust the pH of the system to 7-9, and deionized water is added to adjust the non-volatile matter content of the system to 4%. After stirring for 30 minutes, an acrylic copolymer dispersant is obtained.
[0097] Preparation of single-walled carbon nanotube dispersion
[0098] Single-walled carbon nanotubes, the acrylic copolymer dispersant and deionized water are mixed to obtain a carbon nanotube dispersion slurry with a non-volatile content of 1wt%; wherein the mass proportions of carbon nanotubes and dispersant solids in the slurry are 0.4wt% and 0.6wt%, respectively; after stirring the dispersed slurry, an ultrasonic treatment with an ultrasonic frequency of 20 Hz is performed using a cell disruptor, and after 4 hours, a single-walled carbon nanotube dispersion is obtained by filtering.
[0099] Preparation of negative electrode
[0100] (1) Based on the solid mass, 0.5 parts by mass of conductive carbon black, 9 parts by mass of SiC, 88 parts by mass of graphite, 100 parts by mass of deionized water, 0.5 parts by mass of single-walled carbon nanotube dispersion and 2 parts by mass of polyacrylic acid solution binder were mixed, and the mixture was stirred at a high speed of 2000 r / min for 30 min to obtain a negative electrode slurry.
[0101] (2) The filtered negative electrode slurry was evenly coated on the surface of the copper foil current collector with a coating thickness of 300 μm; then, the current collector coated with the negative electrode slurry was placed in a 90° C. oven and dried for 5 min to obtain a negative electrode sheet.
[0102] Examples 1 to 17 all use the above process to prepare dispersants (compositions of acrylic copolymers), single-walled carbon nanotube dispersions and negative electrode sheets. The difference lies in the types and amounts of raw materials used, see Table 1 for details.
[0103] Comparative Examples 1 to 4
[0104] Comparative Examples 1 to 4 use substantially the same raw materials and processes as those of the above examples to prepare dispersants, single-walled carbon nanotube dispersions and negative electrode sheets, the difference being the types and amounts of the raw materials used, see Table 2 for details.
[0105] The single-walled carbon nanotube dispersions prepared in each embodiment and comparative example were diluted 500 times with deionized water, and whether there were obvious particles dispersed in the water was observed. The presence of obvious particles indicated poor dispersibility, and the absence of obvious particles indicated good dispersion. The specific results are shown in Table 3. The single-walled carbon nanotube dispersions prepared in each embodiment and comparative example were allowed to stand at room temperature for 14 days (14d), and then diluted 500 times with deionized water, and whether there were obvious particles dispersed in the water was observed. The results are shown in Table 3.
[0106] The single-walled carbon nanotube dispersions prepared in the examples and comparative examples were left to stand at room temperature for 14 days, and then the non-volatile content in the upper and lower parts of the dispersions was measured according to the aforementioned method. The results are shown in Table 3.
[0107] The negative electrode sheets prepared in each embodiment and comparative example were tested for peeling force according to the aforementioned method. The results are shown in Table 3.
[0108] Table 1 Raw materials and dosage used in each example (g)
[0109]
[0110]
[0111] Table 2 Raw materials and dosage used in each comparative example (g)
[0112]
[0113] Table 3 Test results of stability, peeling force and electrode sheet of single-walled carbon nanotube dispersion
[0114]
[0115]
[0116] According to the results in Table 3, the non-volatile content of the upper liquid and the non-volatile content of the lower liquid of the single-walled carbon nanotube dispersion prepared in Examples 1 to 17 are not much different after standing for 14 days, indicating that the dispersion has no obvious floating or sedimentation and has good storage stability. In addition, the dilution state of the dispersion after standing for 0 days and 14 days in Table 3 (good permeability and no particles) shows that the single-walled carbon nanotube dispersion has good dispersibility and long-term storage stability; the surface state of the negative electrode sheet shows that the negative electrode slurry has good dispersibility.
[0117] Furthermore, according to the data of the peeling force before and after the electrical activation in Table 3, it can be seen that the peeling force of the negative electrode sheets of Examples 1 to 17 is significantly improved after the electrical activation.
[0118] According to Tables 1 and 2, compared with Example 2, propylene carbonate is used to replace dibutyl itaconate in Comparative Example 1. According to the results of Table 3, a large number of insoluble particles exist in the dispersion of Comparative Example 1 after standing for 14 days, indicating that its stable state is poor. Therefore, the acrylic copolymer using dibutyl itaconate monomer has a better dispersion effect on single-walled carbon nanotubes than the acrylic copolymer using propylene carbonate monomer under the same conditions.
[0119] Furthermore, the amount of dibutyl itaconate used in Comparative Example 2 is low, accounting for 2.4% of the mass content of the polymerized monomers. According to the results in Table 3, after the dispersion of Comparative Example 2 was left to stand for 14 days, the non-volatile content of the upper liquid and the non-volatile content of the lower liquid differed greatly, and a large number of insoluble particles appeared, indicating that the dispersion and stability of the dispersion were poor. Therefore, the amount of dibutyl itaconate used will have a significant effect on the dispersibility and stability of the dispersion. Preferably, based on the total mass of the polymerized monomers, the mass content of itaconate diester is 4 to 8%.
[0120] According to Tables 1 and 2, compared with Example 2, Comparative Example 3 does not use an amphiphilic monomer containing a carbon-carbon double bond. According to the results of Table 3, after the dispersion of Comparative Example 3 was left to stand for 14 days, the non-volatile content of the upper liquid and the non-volatile content of the lower liquid differed greatly, and a large number of insoluble particles appeared, indicating that the dispersion and stability of the dispersion were poor. Therefore, the use of an amphiphilic monomer containing a carbon-carbon double bond will have a significant effect on the dispersibility and stability of the dispersion.
[0121] According to Tables 1 and 2, compared with Example 15, N,N-methylenebisacrylamide is used in Comparative Example 4 to replace the diaziridine crosslinking agent. According to the results in Table 3, the peeling forces of the negative electrode sheets of Example 15 and Comparative Example 4 are similar before electrical activation, but after electrical activation, the peeling force of the electrode sheet of Example 15 increases significantly, while the peeling force of the electrode sheet of Comparative Example 4 changes little, indicating that the diaziridine compound of Example 15 undergoes crosslinking under electrical activation, providing a strong bonding strength for the electrode sheet.
[0122] Based on the above results, the acrylic copolymer composition of the embodiment of the present invention can achieve uniform dispersion of single-walled carbon nanotubes in the aqueous phase, and make the dispersion have excellent long-term storage stability. At the same time, it has a strong interaction with both the current collector and the active material under the action of electricity, thereby improving the peeling force of the prepared electrode sheet.
[0123] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.
[0124] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.
Claims
1. An acrylic copolymer, prepared by polymerizing monomers; the polymerizing monomers include carboxylic acids containing carbon-carbon double bonds, acrylonitrile, styrene, acrylamide, acrylate, itaconate diester and amphiphilic monomers containing carbon-carbon double bonds; The amphiphilic monomer containing carbon-carbon double bonds includes one or more of acrylic acid polyether phosphate, diisooctyl maleate, allyloxy nonylphenol polyoxyethylene ether, and 2-acrylamide-2-methylpropane sulfonic acid.
2. The copolymer according to claim 1, wherein Based on the total mass of the polymerized monomers, the mass content of the carboxylic acid containing a carbon-carbon double bond is 30-40%, the mass content of the acrylonitrile is 20-35%, the mass content of the styrene is 5-10%, the mass content of the acrylamide is 8-12%, the mass content of the acrylic ester is 15-20%, the mass content of the itaconate diester is 4-8%, and the mass content of the amphiphilic monomer containing a carbon-carbon double bond is 2-6%; and / or, The carboxylic acid containing a carbon-carbon double bond contains 3 to 6 carbon atoms.
3. The copolymer according to claim 1, wherein The carboxylic acid containing a carbon-carbon double bond includes one or more of acrylic acid, methacrylic acid, itaconic acid, crotonic acid, fumaric acid and maleic acid; and / or, The acrylic acid ester includes one or more of ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, and isooctyl methacrylate; and / or, The itaconate diester includes dibutyl itaconate. 4 . An acrylic copolymer composition, comprising the acrylic copolymer according to claim 1 and a crosslinking agent, wherein the crosslinking agent comprises a difunctional diaziridine compound.
5. The composition according to claim 4, wherein Based on the total mass of the polymerizable monomers, the mass content of the crosslinking agent in the composition is 0.2-0.5%; and / or, The composition comprises the acrylic copolymer, the crosslinking agent and water; and / or, The difunctional diaziridine compound includes one or two of the following compounds:
6. Use of the acrylic copolymer according to any one of claims 1 to 3 or the acrylic copolymer composition according to claim 4 or 5 as a dispersant for single-walled carbon nanotubes or for preparing a negative electrode for a lithium battery. 7 . A single-walled carbon nanotube dispersion comprising the acrylic copolymer according to claim 1 or the acrylic copolymer composition according to claim 4 and single-walled carbon nanotubes. 8 . A negative electrode slurry comprising the acrylic copolymer composition according to claim 4 or 5 or the single-walled carbon nanotube dispersion according to claim 7 .
9. A negative electrode sheet, the raw materials for preparing the negative electrode sheet include the negative electrode slurry according to claim 8.
10. A lithium battery comprising the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Polyacrylate dispersing agent containing polyfunctional groups and preparation method thereof
CN112279954A
Preparation method and application of aqueous polymer dispersant for inorganic powder
CN115975101A
Copolymers, preparation thereof and use as wetting agents and dispersants
CN1749288A
Copolymer for dispersant for cement, dispersant for cement, and cement composition
US20150065615A1
Toner process comprising synthesizing amphiphilic block copolymers via emulsion polymerization
US9958797B1